Tight oil developments in Russia - James Henderson (The Oxford Institute for Energy Studies, 2013)
Oil production from Russia's core regions is in decline and the government is keen to encourage the development of fields in new areas in order to keep the country's output above 10mmbpd. A series of joint ventures between state oil company Rosneft and various IOCs offshore in the Arctic has caused much excitement in this regard, but the potential of Russia's unconventional oil resources might provide a shorter term reason to be optimistic. Russia has the largest estimated shale oil resources in the world, with a particular focus on the Bazhenov layer, and this report analyses the oil company work that has been done to date to assess the real potential of this resource and also assesses the potential impact of tax changes that have been introduced to encourage investment activity. It concludes that although the resource base would appear to be enormous, a number of below and above ground issues remain which mean that government targets of 1mmbpd of production win a decade are unlikely to be met. Not the least of the challenges to be faced include the need to increase the horizontal drilling capacity of the service industry in Russia as well as the likely need for further tax incentives once a clearer picture of the real economics of unconventional development in Russia has been formed. Nevertheless Russia's unconventional oil plays can make a significant contribution to the country's longer term production outlook in tandem with other developments in the Arctic and East Siberia.
Keywords: 330; Erdölvorkommen; Erdölgewinnung; Russland